PENGEMBANGAN KOMPETENSI SDM DALAM RANGKA MENINGKATKAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DI PROVINSI BALI - Damanik, Siti Nurmawan; Sihotang, Erikson (Jurnal Ilmiah Raad Kertha, 2024)
Implementation of the Government Agency Performance Accountability System (SAKIP) is important in efforts to strengthen Government Agency Performance Accountability reports or AKIP, in order to realize government administration that is free of corruption, collusion and nepotism (KKN). Accountability for the performance of government agencies is the obligation of every Regional Apparatus to account for the success or failure of implementing programs or activities in order to achieve the organization's mission in a measurable manner, performance targets which will be compiled into a government agency performance report (LKjIP) periodically every year. The implementation of SAKIP is carried out to produce quality performance accountability reports by referring to the Presidential Regulation of the Republic of Indonesia Number 29 of 2014 concerning the Performance Accountability System for Government Agencies and other statutory regulations. The preparation of the LKjIP for regional apparatus is carried out every year by referring to the Regulation of the Minister for Use of State Apparatus and RB Number 53 of 2014 concerning Technical Instructions for the Preparation of Agency Performance Agreements, Performance Reporting and Procedures for Reviewing Government Agency Performance Reports.